Species Dependence of SYTO 9 Staining of Bacteria - McGoverin, Cushla; Robertson, Julia; Jonmohamadi, Yaqub; Swift, Simon; Vanholsbeeck, Frédérique (Frontiers in Microbiology, 2020)
SYTO 9 is a fluorescent nucleic acid stain that is widely used in microbiology, particularly for fluorescence microscopy and flow cytometry analyses. Fluorimetry-based analysis, i.e. analysis of fluorescence intensity from a bulk sample measurement, is more cost effective, rapid and accessible than microscopy or flow cytometry but requires application-specific calibration. Here we show the relevance of SYTO 9 for food safety analysis. We stained four bacterial species of relevance to food safety (Bacillus cereus, Escherichia coli, Salmonella enterica subspecies enterica ser. Typhimurium, Staphylococcus aureus) with different concentrations of SYTO 9, with and without the presence of ethylenediaminetetraacetic acid (EDTA), for varying amounts of time, to investigate the effect of these treatment parameters on fluorescence intensity. The addition of EDTA and an increased staining duration did not significantly affect fluorescence intensity, and over the bacterial cell concentration range investigated (~105 – 108 CFU/ml) there was no significant difference in using 0.5 or 1 µM SYTO 9. The effect of bacterial cell concentration on fluorescence intensity was species specific. At different bacterial cell concentrations, the effect of species on fluorescence intensity is different. This interaction complicates the development of a general fluorimetry-based protocol for the determination of bacterial cell concentration in a mixed bacterial suspension, as would be expected from samples taken from food safety settings.